Plant-Mediated Biosynthesis and Photocatalysis Activities of Zinc Oxide Nanoparticles: A Prospect towards Dyes Mineralization. (11th March 2021) - Fagier, Mohamed Awad
Abstract : In recent years, nanoparticles synthesis by green synthesis has gained extensive attention as a facile, inexpensive, and environmentally friendly method compared with chemical and physical synthesis methods. This review covered the biosynthesis of zinc oxide nanoparticles (ZnO NPs), including the procedure and mechanism. Factors affecting the formation of ZnO NPs are discussed. The presence of active bioorganic molecules in plant extract played a vital role in the formation of ZnO NPs as a natural green medium in the metallic ion reduction processes. ZnO NPs exhibit attractive photocatalysis properties due to electrochemical stability, high electron mobility, and large surface area. In this review, the procedure and mechanism of the ZnO photocatalysis process are studied. The effects of dyes amount, catalysts, and light on photodegradation efficiency are also considered. This review provides useful information for researchers who are dealing with green synthesis of ZnO NPs. Moreover, it can provide investigators with different perceptions towards the efficiency of biosynthesized ZnO NPs on dyes degradation and its restrictions.